X, Y theories as sources for effective communication targeting - Naumova, Natalya; Yevstihnieieva, Olena (Lviv Polytechnic Publishing House, 2016)
In theses the role of the X, Y theories as sources for effective communication targeting are shown.
Keywords: X, Y theories; target; goals; responsibilities